Ocular toxoplasmosis associated with scleritis - Kamath, Yogish S (Medknow Publications & Media Pvt Ltd, 2013)
We report an atypical presentation of Toxoplasma retinochoroiditis with associated scleritis in a young and immunocompetent patient. The diagnosis was done on the basis of Polymerase chain reaction of vitreous sample, and the clinical response to specific treatment. This case highlights the unusual presentation of ocular toxoplasmosis as scleritis.